Strategi Komunikasi Branding Dalam Upaya Peningkatan Jumlah Peserta Didik Baru di SMA IT Ash-Shiddiiqi Jambi - Rita Fitria (Al-fahim : Jurnal Manajemen Pendidikan Islam, 2024)
Schools are producers providing educational services. The products offered by schools must be able to attract the interest of consumers, namely parents and students, so that they can attend school there. Schools need to determine strategies to increase their competitiveness through institutional branding or imaging. One branding strategy that can be used is brand communication. This research aims to describe brand communication strategies in an effort to increase the number of new students at Ash-Shiddiiqi Jambi IT High School. This research is qualitative research with a descriptive approach. The data collection technique is through observation, interviews and documentation taken directly from informants, namely the principal, teachers, administration department, employees, students, parents and supervisors of Ash-Shiddiiqi Jambi IT High School. The data analysis technique used is through data reduction, data presentation and drawing conclusions. The results of research at Ash-Shiddiiqi IT High School show that Ash-Shiddiiqi IT High School uses brand communication internally and externally through school stakeholders, uses communication tools and carries out promotions. This strategy is reflected in the SMA IT Ash-Shiddiiqi brand tagline, namely Today's School, Qur'ani Generation, Achievement Generation.